Platelet serotonin modulates immune functions - Mauler, M.; Bode, C.; Duerschmied, D. (Hämostaseologie, 2016)
This short review addresses immune functions of platelet serotonin. Platelets transport serotonin at a high concentration in dense granules and release it upon activation. Besides haemostatic, vasotonic and developmental modulation, serotonin also influences a variety of immune functions (mediated by different serotonin receptors). First, platelet serotonergic effects are directed against invading pathogens via activation and proliferation of lymphocytes, modulation of cytokine release, and recruitment of neutrophils to sites of acute inflammation by induction of selectin expression on endothelial cells. Second, serotonin levels are elevated in autoimmune diseases, such as asthma or rheumatoid arthritis, and during tissue regeneration after ischemia of myocardium or brain. Specific antagonism of serotonin receptors appears to improve survival after myocardial infarction or sepsis and to attenuate asthmatic attacks in animal models. It will be of great clinical relevance if these findings can be translated into human applications. In conclusion, targeting immune modulatory effects of platelet serotonin may provide novel therapeutic options for common health problems.Blutplättchen transportieren Serotonin in hoher Konzentration in ihren Delta-Granula und sezernieren es, wenn sie aktiviert werden. Neben der Modulation von Hämostase, Gefäßtonus und der Organentwicklung beeinflusst Serotonin verschiedene Immunfunktionen, die durch Serotoninrezeptoren vermittelt werden. Zum einen richtet sich der Effekt von Serotonin gegen eindringende Pathogene durch Aktivierung und Proliferation von Lymphozyten sowie die Beeinflussung der Zyto kinsekretion. Auch die Rekrutierung von Neutrophilen hin zu akuten Entzündungsherden verstärkt thrombozytäres Serotonin durch Regulierung der Selektinexpression auf Endothelzellen. Zum anderen sind die Serotoninspiegel in Autoimmunerkrankungen wie Asthma bronchiale oder rheumatoider Arthritis sowie während der Regenerierung von Gewebe nach einem Herzinfarkt oder Schlaganfall erhöht. In Tiermodellen kann die spezifische Antagonisierung von Serotoninrezeptoren das Überleben nach Herzinfarkt oder Sepsis verbessern und asthmatische Anfälle lindern. Die komplexen Immunfunktionen von Serotonin bieten somit möglicherweise neue therapeutische Ansatzpunkte bei schweren Erkrankungen.
Keywords: Inflammatory mediators; platelet immunology; leukocyte function; leukocyte activation